2010
DOI: 10.1038/ismej.2010.138
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality and resource availability control bacterial and archaeal communities in soils of a temperate beech forest

Abstract: It was hypothesized that seasonality and resource availability altered through tree girdling were major determinants of the phylogenetic composition of the archaeal and bacterial community in a temperate beech forest soil. During a 2-year field experiment, involving girdling of beech trees to intercept the transfer of easily available carbon (C) from the canopy to roots, members of the dominant phylogenetic microbial phyla residing in top soils under girdled versus untreated control trees were monitored at bim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
180
5
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 290 publications
(216 citation statements)
references
References 75 publications
22
180
5
3
Order By: Relevance
“…Similar to previous studies, we found a significant influence of seasonality on soil microbial community composition (Kaiser et al 2010;Koranda et al 2013;Rasche et al 2011). From summer to winter, bacterial and fungal PLFA markers increased slightly.…”
Section: Soil Microbial Community Compositionsupporting
confidence: 78%
“…Similar to previous studies, we found a significant influence of seasonality on soil microbial community composition (Kaiser et al 2010;Koranda et al 2013;Rasche et al 2011). From summer to winter, bacterial and fungal PLFA markers increased slightly.…”
Section: Soil Microbial Community Compositionsupporting
confidence: 78%
“…Temperature has a negative correlation with bacterial amoA gene copy numbers and a positive correlation with thaumarchaeal amoA gene copy numbers in a temperate beech forest soil (Rasche et al 2011). The AOA amoA gene copy numbers decreased along an altitudinal gradient of Mount Everest, whereas that of AOB did not shift significantly with altitude (Zhang et al 2009).…”
Section: Responses Of Aob and Aoa Abundance To Soil Warming And Fertimentioning
confidence: 97%
“…1b). The effects of temperature on the amoA gene copy numbers of AOB and AOA have been observed in seasonal or altitude changes (He et al 2007;Zhang et al 2009;Rasche et al 2011). For example, AOB and AOA amoA gene copy numbers have been found to be higher in summer than winter in a Chinese upland red soil (He et al 2007).…”
Section: Responses Of Aob and Aoa Abundance To Soil Warming And Fertimentioning
confidence: 99%
“…Even within DNA-based methods, the differences in DNA extraction methods, DNA yield, the choice of primer sets, as well as qPCR efficiencies, limit the transferability of the results to other studied ecosystems [53]. Nevertheless, both nir genes are known to correlate with soil net N 2 O fluxes [33,[54][55][56]. nirS-possessing organisms usually are comprised of nosZ genes which enable complete denitrification, while nirK organisms mostly lack nosZ [57].…”
Section: The Varying Effects On Denitrification Genesmentioning
confidence: 99%